Small Bowel Gastrointestinal Bleeding Diagnosis and Management—A Narrative Review - Murphy, B.; Winter, D. C.; Kavanagh, D. O. (Frontiers in Surgery, 2019)
Background Small bowel bleeding accounts for 5-10% of all gastrointestinal bleeding. Despite advances in imaging, endoscopy and minimally invasive therapeutic techniques, its diagnosis and treatment remains a challenge and a standardised algorithm for approaching suspected small bowel bleeding remains elusive. Furthermore, the choice of investigation is subject to timing of presentation and accessibility to investigations. The aim of this study was to construct a narrative review of recent literature surrounding the diagnosis and management of small bowel bleeding. Methods A literature review was conducted examining the database pubmed with the following key words and Boolean operators: occult GI bleed OR mesenteric bleed) OR gastrointestinal haemorrhage) OR GI haemorrhage) AND management. Articles were selected and reviewed based on relevance to the research topic. Where necessary, the full text was sought to further assess relevance. Results In overt GI bleeding, CT angiography and red cell scintigraphy are both feasible and reliable diagnostic imaging modalities if standard endoscopy is negative. Red cell scintigraphy may be advantageous through detection of lower bleeding rates but it is subject to availability. Overt bleeding and a positive CT angiogram or red cell scan improves the diagnostic yield of formal angiography +/- embolisation. Video capsule endoscopy or double balloon endoscopy can be considered in occult GI bleeding following normal upper and lower endoscopy. Conclusions Small bowel bleeding remains a rare but significant diagnostic and therapeutic challenge. Technological advances in diagnostics have aided evaluation but have not broadened the range of therapeutic interventions.